Cohesive energy effects in the atomic transport induced by ion beam mixing - Chang, GS; Jung, SM; Song, JH; Kim, HB; Woo, JJ; Byun, DH; Whang, CN (ELSEVIER SCIENCE BV, 1997)
Atomic transport in the radiation enhanced diffusion (RED) region has been studied from the shifts of a marker layer in ion beam mixed Pd/Co and Pd/Au bilayers, 80 keV Ar+ with a dose of 1.5 x 10(16) ions/cm(2) were irradiated into the bilayers at temperature region from 90 K to 700 K. In the Pd/Co system, the atomic flux of Pd (J(Pd)) transported across the interface is nearly same with J(Co) in the thermal spike region, while J(Pd) is always larger than J(Co) in the RED region. However, in the Pd/Au system, J(Pd) is nearly same with J(Au) in both of the thermal spike and RED regions. We have developed a model to describe the atomic transport in the RED region, which predicts that the atom with small cohesive energy has more mobility than that with large cohesive energy.
Keywords: ANISOTROPIC TRANSPORT; IMPURITY DIFFUSION; FCC METALS; SEGREGATION; ALLOYS